A new species of stag beetle from sand dunes in west Texas, and a synopsis of the genus Nicagus (Coleoptera: Lucanidae: Aesalinae: Nicagini) - Paulsen, M. J.; Smith, Aaron D. (Zootaxa, 2005)
A new species of stag beetle, Nicagus occultus n. sp., is described from the Monahans Sandhills of western Texas. Previously, the genus Nicagus contained only two species: N. obscurus (LeConte) from the eastern and central United States and southern Canada, and N. japonicus Nagel from Japan. The discovery of N. occultus represents both an unexpected range extension and an unusual habitat (unvegetated sand dunes) for the family Lucanidae. A synopsis (diagnosis and distribution) for each Nicagus species is given, including detailed distributional information for N. obscurus.